Discrete-Time Filter Synthesis using Product of Gegenbauer Polynomials - Stojanovic, Nikola; Stamenkovic, Negovan; Krstic, Ivan (Společnost pro radioelektronické inženýrství, 2016)
A new approximation to design continuoustime and discrete-time low-pass filters, presented in this paper, based on the product of Gegenbauer polynomials, provides the ability of more flexible adjustment of passband and stopband responses. The design is achieved taking into account a prescribed specification, leading to a better trade-off among the magnitude and group delay responses. Many well-known continuous-time and discrete-time transitional filter based on the classical polynomial approximations(Chebyshev, Legendre, Butterworth) are shown to be a special cases of proposed approximation method.
Keywords: Gegenbauer polynomials; lowpass filters; continuous-time filters; discrete-time filters